The Study on Extraction Technology of Flavonoids from Tribute Citru Peel. Issue 1 (September 2020) - Wu, Ya; Hu, Chengming; Chen, Xinxing; Su, Xiaofei; Zhao, Xin
Abstract: Tribute Citru peel is rich in various natural products. Total flavonoids from Tribute Citru peel were extracted by solvent extraction method and the content of total flavonoids was determined by UV spectrophotometer with rutin as standard. The effects of reflux time, solidliquid ratio, ethanol concentration and temperature on the extraction of flavonoids were investigated. The optimum condition determined by orthogonal test was that Tribute Citru peel and 80% ethanol were mixed in the solid-liquid ratio of 1:20, then heated for 4h at 90 °C. Under this condition, the extraction rate yield of flavonoids reached 1.43%.